DETERMINAN KESUKSESAN APLIKASI SIA KOMDANAS PADA SATUAN KERJA DI KOORDINATOR WILAYAH PENGADILAN TINGGI MATARAM - Lalu Afghan Muharor; B. Busaini; Nur Fitriah (Universitas Trunojoyo Madura, 2015)
The objective of this study is to examine the positive effect of information system quality, information quality and service quality on user satisfaction and use of system, the effect of use of system to user satisfaction, the effect of user satisfaction on use of system, the effect of use on net benefits and the effect of user satisfaction on net benefits. Data used in this study is primary data based on questionnaires distributed to the users of komdanas who work at work unit under the regional coordinators Pengadilan Tinggi Mataram. In this study, I use smart partial least square to examine 102 returned questionnaires. The results of this study show that information quality statistically positive affects the use of system but statistically negative affects the user satisfaction, system quality statistically positive affects the use of system and user satisfaction, service quality statistically positive affects the user satisfaction but statistically negative affects the use of system, use of system statistically positive affects the user satisfaction, user satisfaction statistically positive affects the use of system, use of system statistically did not affect the net benefits and user satisfaction statistically positive affects the net benefits.